Percutaneous Removal of Foreign Bodies From the Bile Ducts - S. A. Prozorov; P. A. Ivanov (Неотложная медицинская помощь)
In minimally invasive treatment of obstructive jaundice, complications may occasionally occur: separation of a fragment of a conductor, drainage, balloon catheter, poor function of a plastic endoprosthesis. There are two possible methods for percutaneous removal of foreign bodies: extraction and pushing into the duodenum. Two observations of percutaneous removal of conductor fragments from the bile ducts are presented.